Chronic and Episodic Stress in Children of Depressed Mothers. Issue 3 (3rd May 2016) - Feurer, Cope; Hammen, Constance L.; Gibb, Brandon E.
Abstract : The goal of this study was to examine chronic and episodic stress in children of mothers with and without a history of major depressive disorder (MDD) during the children's lives. Participants were 255 mothers selected according to their history of MDD (present vs. absent during child's life) and their children (age 8–14; 53% girls, 81% Caucasian). Mothers' and children's histories of MDD were assessed using diagnostic interviews, and their depressive symptoms were assessed via self-report measures. Children's levels of chronic and episodic stress were assessed using a semistructured contextual threat interview. Children of mothers with a history of recurrent MDD, compared to single MDD or no depression, experienced more chronic stress within several domains including peers, mother–child relations, and other family member relations as well as greater episodic dependent interpersonal stress. Each of these group differences was maintained after excluding children with a history of MDD themselves and controlling for their current depressive symptoms. However, only the group difference in chronic peer stress was maintained when controlling for mothers' current depression. The results suggest that children exposed to recurrent maternal MDD experience higher levels of both chronic and episodic stress, at least some of which they contribute to themselves (dependent interpersonal stress) and which is at least partially independent of the effects of children's depression. In addition, much of this stress is associated primarily with current depression in the mother, though it appears that chronic peer stress may remain elevated even after the remission of maternal depression.